Partiklar i sørsamisk - Trosterud, Trond (Septentrio Academic Publishing, 2023)
The article presents the most central particles in Southern Sami, and argues that they constitute a separate part of speech different from adverbs. Most particles usually occur in the second position of the sentence, but several particles may also occur in second position in complex verb phrases, i.e. in third position in the sentence. A group of words have in previous research been treated as both proclitic and enclitic particles, it is argued here that these should be treated as adverbs. Artikkelen går gjennom dei mest sentrale partiklane i sørsamisk, og argumenterer for at dei utgjer ei separat ordklasse separat frå adverba. Dei fleste partiklane står som regel i andre posisjon i setninga, men ein stor del av desse kan også stå i andre posisjon i komplekse verbfrasar, dvs. i tredje posisjon i setninga. Ei gruppe av ord har i tidlegare forsking vorte handsama som både proklitiske og enklitiske partiklar, det blir her argumentert for at desse bør bli handsama som adverb.